Front Cover. Issue 6 (4th May 2016) - Maruyama, Pietro K.; Vizentin‐Bugoni, Jeferson; Sonne, Jesper; Martín González, Ana M.; Schleuning, Matthias; Araujo, Andréa C.; Baquero, Andrea C.; Cardona, Juliana; Cardona, Paola; Cotton, Peter A.; Kohler, Glauco; Lara, Carlos; et al.
Abstract : The cover image, by Pietro K. Maruyama et al ., is based on the Biodiversity Research. The integration of alien plants in mutualistic plant–hummingbird networks across the Americas: the importance of species traits and insularity, DOI:10.1111/ddi.12434 .